HUBUNGAN MEDIA WEBSITE PT. GARUDA INDONESIA DENGAN MINAT CALON PENUMPANG ROUTE JAKARTA-AMSTERDAM - Maulana, Indra (Universitas Prof. Dr. Moestopo (Beragama), 2012)
Garuda Indonesia is the flag carrier airline Indonesia. Reopening route Jakarta-Amsterdam is the international news route Garuda Indonesia with airbus A 333-200. Promotion for that new route using many media include website. Website Garuda Indonesia is interactive media that give the user or browser can find the information anytime and anywhere. Website is fast, no space limitations, allows you to accodate the receiver-driven nature of information-economy communication, and opens the opportunity to engage in one-to-one communication and marketing. This research focusing the correlation between website Garuda Indonesia with buying interest.